2007
DOI: 10.1128/jcm.00558-07
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus iners : a Marker of Changes in the Vaginal Flora?

Abstract: ᰔLactobacillus iners seems to be a species of lactobacilli occurring in the human vagina that deserves close scrutiny, as it was not found in earlier studies due to its peculiar culture requirements but is now discussed as one of the normal vaginal bacteria (1,4). Following up on the interesting paper by Ferris et al. on changes in vaginal flora after the treatment of bacterial vaginosis with metronidazole, and especially their finding of L. iners DNA clones posttreatment, we would like to add to the picture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
60
5
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 4 publications
10
60
5
1
Order By: Relevance
“…A similar increase in numbers of Treg cells was found in subjects colonized only by L. iners compared to the results seen with those with only L. crispatus. Previously, L. crispatus has been suggested to be more often linked with health and L. iners with disease (25). No clear immunological support was found for this claim in this study population.…”
Section: Discussioncontrasting
confidence: 53%
“…A similar increase in numbers of Treg cells was found in subjects colonized only by L. iners compared to the results seen with those with only L. crispatus. Previously, L. crispatus has been suggested to be more often linked with health and L. iners with disease (25). No clear immunological support was found for this claim in this study population.…”
Section: Discussioncontrasting
confidence: 53%
“…second type of harmful bacteria represented by Gardnerella vaginalis and Peptostreptococcus anaerobius. Our findings align with those of Jakobsson and Forsum [12] who have suggested that L. iners is a dominant part of the cervicovaginal flora when the flora is in a transitional stage between abnormal and normal. Moreover, Gardnerella vaginalis and Peptostreptococcus anaerobius have been reported to be the most acid resistant of the harmful species [7], which may Figure 5.…”
Section: Viscosity Of Cervicovaginal (Centipoise)supporting
confidence: 81%
“…L. iners is the dominant species in the vaginal flora when the flora is in a transitional stage between normal and abnormal, because of either treatment with antibiotics or physiological changes such as higher plasma estradiol levels (24). Estrogen may be the most probable factor contributing to a predominance of L. iners in the obese women of this study.…”
Section: Discussionmentioning
confidence: 90%